Individual differences in interrupted task performance: One size does not fit all. Issue 79 (July 2015) - Drews, Frank A.; Musters, Adrian
Abstract: Two experiments used a spatial navigation task to study the relationship between individual differences in working memory capacity and interrupted task performance. The results of experiment one show that participants with low working memory capacity (WMC) are more susceptible to the negative effects of interruptions than participants with high WMC. The results of additional analyses indicate that both groups differ in their strategies used to memorize material from the primary task. A second experiment manipulated memory strategy use for high and low memory span participants and found that low span participants performed at the level of high spans when using a strategy that is more typically used by high span participants. However, this performance improvement did not show during interrupted tasks. Overall, these results suggest that individual memory capacity differences affect performance during interrupted tasks by determining selection of memory strategies and by limiting performance of participants. Highlights: A new paradigm was developed to study task interruptions. Memory differences affect strategy selection and success in dealing with interruptions. Individual memory differences affect performance during interrupted tasks.